Increased number of IL-2, IL-2 receptor and IL-10 positive cells in premalignant lesions of the cervix. - Mindiola, Raimy; Callejas, Diana; Núñez-Troconis, José; Araujo, Mary; Delgado, Mariela; Mosquera, Jesús (Investigación Clínica, 2009)
Previous studies have shown the involvement of the immune response in the progression of human uterine cervix cancer. The aim of this study was to determine the expression of Interleukin-2 (IL-2), IL-2 receptor (IL-2R) and Interleukin 10 (IL-10) in different grades of cervical intraepithelial neoplasias of the exocervix (CIN 1, 2 and 3), and its relationship with the serum cytokine profiles and human papilomavirus (HPV) infection status. Indirect immunofluorescence was used to study the expression of IL-2, IL-2R and IL-10 in human cervical samples from 50 patients and 9 normal controls. Serum IL-2, IL-2R and IL-10 were measured by ELISA and HPV DNA and HPV types were identified by PCR. Increased number of IL-2, IL-2R and IL-10 positive cells were observed in the cervix from patients with CIN, associated with the grades of dysplasia. A significant correlation was observed between IL-2 and IL-2R (p>0.0001), IL-2 and IL-10 (p > 0,0001), as well as IL-10 and IL-2R (p> 0.0001). Twenty percent of patients were HPV positive and 84 % of those patients were tissue cytokine positive. These results suggest that IL-2, IL-2R and IL-10 tissue expression may play a role in the development of cervical intraepithelial dysplasias.